Comparative Genomics of Methanopyrus sp. SNP6 and KOL6 Revealing Genomic Regions of Plasticity Implicated in Extremely Thermophilic Profiles - Yu, Zhiliang; Ma, Yunting; Zhong, Weihong; Qiu, Juanping; Li, Jun (Frontiers in Microbiology, 2017)
Methanopyrus spp. are usually isolated from harsh niches, such as high osmotic pressure and extreme temperature. However, the molecular mechanisms for their environmental adaption are poorly understood. Archaeal species is commonly considered as primitive organism. The evolutional placement of archaea is a fundamental and intriguing scientific question. We sequenced the genomes of Methanopyrus strains SNP6 and KOL6 isolated from the Atlantic and Iceland, respectively. Comparative genomic analysis revealed genetic diversity and instability implicated in niche adaption, including a number of transporter- and integrase/transposase-related genes. Pan-genome analysis also defined the gene pool of Methanopyrus spp., in addition of ~120-Kb genomic region of plasticity impacting cognate genomic architecture. We believe that Methanopyrus genomics could facilitate efficient investigation/recognition of archaeal phylogenetic diverse patterns, as well as improve understanding of biological roles and significance of these versatile microbes.